Incidence of avascular necrosis in patients with sickle cell anemia received hydroxyurea and blood transfusion: a comparative study - Asmaa Hassan Khudhair; Zahraa Mohammed Majeed; Ghassan Hatif Hadi; Talib Abdul-Jaleel Al-Madany; Alaa Jumaah Manji Nasrawi (Zdorovʹe Rebenka, 2024)
Background. Sickle cell anemia is the most common hereditary disease recognized as a priority public health problem. Vaso-occlusive crises, particularly avascular necrosis (AVN), are one of its serious complications; early detection and proper treatment of AVN prevent or reduce its worse progression. The purpose of the study: to compare the incidence rates of avascular necrosis in pediatric patients with sickle cell anemia who received hydroxyurea and blood transfusions. Materials and methods. A prospective comparative study was conducted at Al Zahra Teaching Hospital in Al Najaf from November 2022 to October 2023, and included 43 patients who received hydroxyurea and 70 people on blood transfusion. Avascular necrosis was confirmed by X-ray and magnetic resonance imaging, and it was staged according to the Steinberg staging system. Results. The incidence of AVN was 28.3 %, and it was significantly lower in the hydroxyurea than in the blood transfusion group (16.3 vs. 35.7 %). The relative risk was 0.456, indicating a likely protective effect of hydroxyurea against AVN. A significant association was found between the incidence of AVN and advancing age (P < 0.05). Neither incidence nor staging of AVN shows a significant association with gender (P > 0.05). Conclusions. A lower incidence rate and less severe AVN were reported in patients who received hydroxyurea than in those on blood transfusion. AVN was significantly associated with advancing age but was not affected by the gender of patients.